CHARACTERISTICS OF LIPIDS OF WOAD (ISATIS TINCTORIA L.) SEEDS - Tillayeva Gulnora Urunbayevna; Khakimjanova Shakhnoza Ozod kizi (Scholars Digest Publishing, 2024)
The article presents the results of studies of Woad seeds and presents these characteristics of seed lipids, fatty acid composition of neutral lipids, glycolipids and phospholipids of seeds. The qualitative composition of unsaponifiable substances was determined by the TLC method. The qualitative composition of unsaponifiable substances was determined by the TLC method. The Folch method was used to extract a polar lipid concentrate consisting of residues of neutral lipids, glycolipids and phospholipids. The carotenoid content in unsaponifiable substances was determined by the spectrophotometric method. Biologically active components such as hydrocarbons, carotenoids, free fatty acids, free phytosterols and triterpenols have been found among unsaponifiable substances. Sterols were the main component of unsaponifiable substances. Fatty acids were analyzed as methyl esters by the GC method. They were identified by comparing the retention times of their peaks on chromatograms with the retention times of peaks of a standard sample of a mixture of 37 methyl esters of fatty acids. The results of the analysis showed that the seeds contain more than 50% of phospholipids, which are unsaturated fatty acids, which are of great nutritional value, and also have a powerful antioxidant effect: Omega-3, Omega-6 and Omega-9 fatty acids.
Keywords: Seeds of Isatis tinctoria, moisture content, unsaponifiable substances, carotenoids, fatty acid composition, neutral lipids, phospholipids, glycolipids.